Study on the subsurface damage depth of monocrystalline silicon in ultrasonic vibration assisted diamond wire sawing. (December 2021) - Wang, Yan; Zhao, Bocheng; Huang, Shengju; Qian, Zhaofeng
Highlights: A mathematical model of the subsurface damage depth in monocrystalline silicon wafers induced by ultrasonic vibration assisted diamond wire sawing (UAWS) was proposed. The variation of subsurface damage depth with position angle of diamond abrasives under ultrasonic vibration was analyzed on the cross section of wire saw. The influence of shielding effect of median crack on subsurface damage depth under ultrasonic vibration was analyzed. A finite element model of diamond wire sawing monocrystalline silicon was established by ABAQUS, and the subsurface damage depth under different slicing parameters was simulated. The interface bonding method was used to measure the subsurface damage depth of monocrystalline silicon wafer. Abstract: Diamond wire sawing is one of the key technologies in solar cell manufacturing process and semiconductor chip manufacturing process. The subsurface damage depth (SSD) affects the quality of machined surface in diamond wire sawing, which must be evaluated. In this paper, a mathematical model of the SSD in monocrystalline silicon wafers induced by ultrasonic vibration assisted diamond wire sawing (UAWS) was proposed. In this model, the input is the depth and deflection angle of the median crack, the depth and length of the lateral crack, and ultrasonic vibration, and the output is the residual SSD on the chip. According to the model, the variation of SSD with position angle of diamond abrasives under ultrasonic vibration was analyzed on the cross section of wire saw, and the influence of shielding effect about median crack on SSD under ultrasonic vibration was analyzed later. Then, a finite element model (FEM) of diamond wire sawing monocrystalline silicon was established by ABAQUS, and the SSD under different slicing parameters was simulated. Finally, the interface bonding method was used to measure the SSD of monocrystalline silicon wafer. The experimental results showed that the SSD increases with the increase of the wire saw feed rate, and decreases with the increase of the wire saw speed and the workpiece rotation speed. The SSD in wafer sliced by UAWS is 18.95% on average lower than that in wafer sliced by conventional wire sawing (CWS). The maximum error between theoretical of mathematical model and experimental values is 15.9%, which verifies the validity of the mathematical model.